Evaluation of physicochemical composition and bioactivity of a red seaweed (Pyropia orbicularis) as affected by different drying technologies. Issue 9 (11th June 2020) - Uribe, Elsa; Vega-Gálvez, Antonio; García, Vivian; Pastén, Alexis; Rodríguez, Katia; López, Jéssica; Scala, Karina Di
Abstract: The red seaweed Pyropia orbicularis was dried using four different drying methods (freeze-, vacuum-, solar-, and convective-drying) to evaluate the effect of the drying method on physicochemical parameters, phytochemical contents, antioxidant activity, and antimicrobial activity. Freeze- and vacuum-drying resulted in dried samples with the highest total amino acids retention. Solar and convective drying resulted in dried samples with the highest polyunsaturated fatty acids retention. All dried seaweed showed a significant decrease ( p < .05) in the pigments content and antioxidant activity when compared with fresh samples. With respect to the antimicrobial activity, the methanolic extracts of seaweeds showed antifungal activity but not antibacterial activity. In general, freeze-drying resulted in dried samples with the best overall quality.